Analisis Kinerja Karyawan Menggunakan Gaya Kepemimpinan dan Self Efficacy - hery sahrial; Sunaryo Sunaryo (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2021)
The purpose of this study was to analyze employee performance by using the variables of leadership style and self efficacy. This research was conducted at a motor vehicle distributor company in the city of Medan. The sample of this study was 123 people. This research is a survey research using a questionnaire. Data analysis using Structure Equation Modeling (SEM). The results showed that leadership style and self-efficacy are variables that have a significant impact on employee performance. Self Efficacy is the most dominant variable affecting employee performance.